2005
DOI: 10.1111/j.1439-0310.2004.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Snake Species Discrimination by Wild Bonnet Macaques (Macaca radiata)

Abstract: Wild bonnet macaques (Macaca radiata) were studied in southern India to assess their ability to discriminate non-venomous, venomous and predatory snakes. Realistic snake models were presented to eight troops of bonnet macaques at feeding stations and their behavior was video-recorded 3 min before and 3 min after snake exposure. Snakes presented were: (1) venomous Indian cobra (Naja naja) displaying an open hood with ÔeyespotsÕ; (2) venomous common Indian krait (Bungarus caeruleus); (3) non-venomous green keelb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 44 publications
2
58
2
Order By: Relevance
“…Infant monkeys with bilateral neurotoxic lesions of the superior colliculus continue to reach for food in the presence of a snake model, whereas shamoperated monkeys avoid the food (21). Evasive movements such as these are typical of animals that are surprised or threatened by others (22,23). The pulvinar is also connected to the amygdala (24).…”
Section: Discussionmentioning
confidence: 99%
“…Infant monkeys with bilateral neurotoxic lesions of the superior colliculus continue to reach for food in the presence of a snake model, whereas shamoperated monkeys avoid the food (21). Evasive movements such as these are typical of animals that are surprised or threatened by others (22,23). The pulvinar is also connected to the amygdala (24).…”
Section: Discussionmentioning
confidence: 99%
“…Alarm calling is further evidence that primates evolved in the presence of predators, and is also employed differently from species to species. It was shown that vervet monkeys and bonnet macaques have the ability to define species within classes of predators (Seyfarth et al 1980;Ramakrishnan et al 2005), while Diana monkeys also respond differently based on predator hunting style (Zuberbuhler et al 1997). This is evidence that each species has evolved specific mechanisms that are likely suited to the specific needs of their own environments.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Ramakrishnan et al (2005) found bonnet macaques can distinguish between venomous, nonvenomous and predatory snakes. The macaques responded with caution to all snake species, but pythons (Python molurus), the only snakes known to consume bonnet macaques, were the only species that elicited alarm calls (Ramakrishnan et al 2005). This shows that bonnet macaques have the ability to distinguish between snake species, as their main predator prompted the most active response.…”
Section: Alarm Callingmentioning
confidence: 89%
See 2 more Smart Citations